Salvage Low Dose Rate Brachytherapy For Recurrent Prostate Cancer After External Beam Radiotherapy: Results From A Single Institution With Focus On Toxicity And Functional Outcomes. (6th November 2017) - Barbera, F; Triggiani, L; Buglione, M; Ghirardelli, P; Vitali, P; Caraffini, B; Borghetti, P; Greco, D; Bardoscia, L; Pasinetti, N; Costa, L; Maddalo, M; et al.
Background/aim: Low dose rate brachytherapy has been used as salvage therapy for locally recurrent prostate cancer (PC) after primary external beam radiation therapy (EBRT), along with surgery and cryotherapy. All these techniques, in particular, when applied to the whole gland, involve a relatively high risk of toxicity and may worsen the patient's quality of life. Our aim is to evaluate the results of whole-gland salvage brachytherapy (SBT) after primary EBRT in terms of toxicity, functional outcomes, and efficacy. Materials and methods: We retrospectively reviewed clinical data on 19 patients consecutively treated with SBT at our institution between June 2012 and November 2015. Local recurrences were identified with 11C-choline positron emission tomography/computed tomography and pelvic magnetic resonance imaging after biochemical recurrence according to Phoenix criteria (prostate-specific antigen nadir + 2). Low dose rate brachytherapy was performed by 125 I permanent seeds implantation to the whole prostate gland, with a prescription dose of 130 Gy. At the time of SBT, only 2 patients were receiving androgen deprivation therapy. Acute and late toxicities were recorded using the CTCAE 4.0 scoring system. Quality of life was assessed using IPSS (International Prostate Symptoms Score) and IIEF (International Index of Erectile Function) questionnaires at baseline and 6, 12, and 24 months after SBT, and the respective mean values were compared using Student t test. Biochemical relapse-free survival (BRFS) was also calculated. Results: Median follow-up after SBT was 24 months. Of 19 patients, 2 patients experienced a G3 cystitis (10.2%) and 1 patient experienced a G4 proctitis (5.3%), respectively. Mean pre-SBT IPSS scores and 6, 12, and 24 months after SBT were 5.84, 10.22, 15.72, and 8.10, respectively. Mean pre-SBT IIEF scores and 6, 12, and 24 months after SBT were 8.42, 3.55, 7.89, and 6.40, respectively. At the time of analysis, only 2 patients showed a biochemical relapse (3-year BRFS 85.2%). The Student t test demonstrated a worsening of functional outcome 6 months and 1 year after treatment but a subsequent improvement 2 years after SBT. Conclusions: Salvage brachytherapy for recurrent PC after primary EBRT seems to be a feasible treatment for selected patients. Our series revealed a severe toxicity peak 6 months and 1 year after local re-treatment and then they decrease. Early BRFS rates are good. However, these are very preliminary results so further patient accrual, long-term follow-up, and prospective trials are needed in the future.